Peran Komunikasi dan Kerjasama Tim Terhadap Loyalitas Kerja Karyawan pada PT. Boo Young Indonesia - Pebi Komarudin; Djaka Adiwinata; Irawan Irawan (Journal of Management and Creative Business, 2025)
The purpose of this research is to examine the role of communication and teamwork on employee work loyalty at PT. Boo Young Indonesia. This research was conducted using quantitative methods, the population in this study was 150 people. Sampling used the Slovin formula with an unsaturated technique with a sample size of 60 respondents. The data collection technique uses a questionnaire and is distributed directly to PT employees. Boo Young Indonesia. Data analysis using smartPLS 3.0. The results of the research show that communication has an effect on employee loyalty because the t-statistic value is 11,957 > t-table 1.96 and the p-value significance value is 0.000 > 0.05, so communication can be used as a measure of whether an employee has high or low work loyalty. Teamwork has a positive effect on employee loyalty because the t-statistic value is 44,577 > t-table 1.96 and the p-value is 0.000 < 0.05, the better the teamwork, the more it will influence employee loyalty, and vice versa. Communication and teamwork simultaneously have a positive effect on employee loyalty because the variability of the communication construct (X1) and teamwork (X2) is 94.0%, which means they simultaneously have a strong effect due to values ​​above 0.75, so that if communication and teamwork are improved simultaneously the same, then this will affect the loyalty of an employee.